Second Five Year Plan Bombay State District N. Satara - Government of Bombay (Government of Bombay, 1958)
The Second Five-Year Plan (1956–1961) for North Satara District outlines a comprehensive development strategy aimed at strengthening the district’s socio-economic structure through coordinated initiatives in agriculture, irrigation, industry, infrastructure, education, health, and social welfare. With nearly 78% of the district’s population dependent on agriculture and a significant portion of cultivated land vulnerable to water scarcity, the plan prioritizes agricultural development through the distribution of improved seeds, fertilizers, and modern farming techniques to enhance crop productivity for major crops such as bajra, jowar, rice, and mung. Irrigation expansion forms a central component of the strategy, with projects such as bandharas, storage tanks, and the proposed Vir Dam designed to significantly increase irrigated land and reduce reliance on erratic monsoon rainfall. Industrial development initiatives focus on strengthening cottage and village industries while encouraging the establishment of industrial cooperatives and providing financial assistance to stimulate rural employment and local entrepreneurship. Infrastructure improvements include major investments in road construction and transport networks, including the expansion of state highways, railway connectivity, and the nationalization of passenger transport services through the Bombay State Road Transport Corporation to improve regional accessibility. The plan also emphasizes the expansion of power supply infrastructure through improved voltage management and interconnection with regional electricity systems to support industrial and domestic energy needs. Educational development receives considerable attention through the expansion of primary, secondary, and higher educational institutions, the introduction of vocational and physical education programs, and initiatives aimed at increasing literacy levels and youth development through service camps and teacher training. Public health initiatives include the expansion of hospital facilities, establishment of new health centers, and implementation of disease control programs targeting malaria, leprosy, and other communicable diseases, supported by mobile health units and improved healthcare accessibility. Additional development programs address housing needs for low-income groups and industrial workers while implementing welfare initiatives for Scheduled Castes and Scheduled Tribes to promote social inclusion and economic upliftment. Environmental management measures such as afforestation and the cultivation of medicinal plants aim to preserve natural resources and prevent soil erosion. Through integrated community development programs and cooperative movements, the plan encourages local participation and resource mobilization to strengthen rural economies. Overall, the Second Five-Year Plan for North Satara District represents a holistic approach to regional development, focusing on agricultural growth, infrastructure expansion, industrial promotion, social welfare, and environmental sustainability to create a foundation for long-term economic stability and improved living standards.
District N. Satara
District N. Satara
Keywords: State Five Year Plan; North Satara District Development; Agricultural Development Programs; Irrigation Projects and Water Management; Cottage and Village Industries; Industrial Cooperative Development; Road and Transport Infrastructure; Educational Expansion Initiatives; Public Health and Disease Control; Rural Electrification and Power Supply; Community Development Programs; Welfare of Scheduled Castes and Tribes